A structured methodology to peer review disaster risk reduction activities: The Viable System Review. (June 2020) - Shaw, Duncan; Fattoum, Ayham; Moreno, Jenny; Bealt, Jennifer
Abstract: This paper develops a theoretically underpinned peer review approach (called Viable System Review) to assess and strengthen disaster risk reduction (DRR) practices. This topic is timely as countries and cities look to learn lessons from others to respond to global priorities on DRR. Unlike other peer review methodologies which rely on expert intuition to navigate peer review issues, our new methodology structures the peer review process through an organising framework of concepts. That framework is theoretically underpinned by systems thinking and concepts from the Viable System Model which provides a comprehensive, tested approach to assess organisational performance. The paper explores the development and application of our new peer review methodology (which we call Viable System Review) to the policy developed by Concepcion Province (Chile) on involving spontaneous volunteers in disaster situations. The peer review took place over six days, involved seven reviewers, and focused on identifying good practices, opportunities to enhance practice, and lessons they could take back to their home organisations. The paper presents our Viable System Review methodology, reflects on its application, and discusses its practical and theoretical contributions.